Julie Lazes, Conflictualité, distribution et instabilité macroéconomique. Comportements rentiers et modes de régulation en Argentine - Julie Lazes (Revue de la Régulation)
From a sociological approach to conflicting relationships as a process of social creation of links based on G. Simmel’s work, the main focus of this PhD dissertation is on the nature of institutionalized compromise in Argentina and a possible economic reproduction based on violence. We carry out the conclusion that in Argentina, violence is embodied into the rentier’s behavioral dynamics. In this case, violence is articulated with the pursuit of emancipation of the social, economic and political constraint. Even though this feature is inherent to capitalism, it takes an important dimension in a society that has been founded on a high concentration of wealth and, most particularly, in the concentration of land ownership.